"Precision" drug development?. Issue 2 (20th November 2015) - Woodcock, J
Abstract : The concept of precision medicine has entered broad public consciousness, spurred by a string of targeted drug approvals, highlighted by the availability of personal gene sequences, and accompanied by some remarkable claims about the future of medicine. It is likely that precision medicines will require precision drug development programs. What might such programs look like?